THE EFFECT OF FUNDAMENTAL FACTORS AND MACROECONOMIC VARIABLES ON THE CAPITAL BUFFER OF ISLAMIC BANKS - Ulis Fajar Choirotun Hisan; Dina Fitrisia Septiarini (Universitas Airlangga, 2020)
Banks are trust institutions. The tools that are appropriate to support this trust are the capital adequacy of the bank (capital buffer), related to the ability of banks to detect the risks faced. This study discusses the effects of financing risk (NPF), operational risk (BOPO), market risk (NI), profitability (ROA), bank size (SIZE), Gross Domestic Product (GDP), and money exchange (M2) on buffer capital (M2) CAR) BUS in Indonesia during the period 2010-2018, both partially and simultaneously. The data used are quantitative data with panel data regression methods using statistical tools stata13. This research uses secondary data while the study population is 14 Islamic commercial banks which then obtained a sample of 11 BUS based on the purposive sampling method. NPF, NI, SIZE, GDP, and M2 have a significant effect on CAR, where NI and M2 have a positive effect, and NPF, SIZE, GDP affect negatively. Related to expenditure risk variables, market risk, bank size, GDP, and money that can be issued as determined by the BUS capital buffer in Indonesia in the period 2010-2018. Operational Risk (BOPO) and profitability (ROA) have no significant effect on BUS capital buffers (CAR) in the study period. Regarding implementation of Basel III, funding risk and market risk are significant determinants of capital buffers, and capital buffers are found to be procyclical to Indonesia's finances. Keywords: capital buffer, risk profile, macroeconomic conditions, basel III.REFFERENCEAbusharba, M. T., Triyuwono, I. (2013). Determinants of capital adequacy ratio (CAR) in Indonesian islamic commercial banks. Global Review of Accounting and Finance, 4(1), 159-170. Al-Tamimi, Khaled, A. & Samer, F. (2013). Determinants of capital adequacy in commercial banks of Jordan an empirical study. International Journal of Academic Research in Economics and Management Sciences, 2(4), 44-58. http://dx.doi.org/10.6007/IJAREMS/v2-i4/53Andhika, Y. D. & Suprayogi, N. (2016). Determinan capital adequacy ratio (CAR) bank umum syariah di Indonesia. Jurnal Ekonomi Syariah Teori dan Terapan, 4(4), 312-323.Ardi, Murdoko, S. & Lana, Sularto. (2007). Pengaruh ukuran perusahaan, profitabilitas, leverage, dan tipe kepemilikan perusahaan terhadap luas voluntary disclosure laporan keuangan tahunan. Jurnal Penelitian, 2, 53-61.Awojobi, O., Amel, R., & Norouzi, S. (2011). Analysing risk management in banks: Evidence of bank efficiency and macroeconomic impact. Journal of Money, Investment and Banking. Euro Journals Publishing, Inc. (22) http://mpra.ub.uni-muenchen.de/33590/Baltagi, B. H. (2005). Econometric analysis of panel data. Chichester: John Willwy & Sons.BI. (2011). Peraturan Bank Indonesia No 13/1/PBI/2011 tentang Penilaian Tingkat Kesehatan Bank Umum. Jakarta: Bank Indonesia.__. (2013). Peraturan Bank Indonesia Nomor 15/12/PBI/2013 tentang Kewajiban Penyediaan Modal Minimum Bank Umum. Jakarta: Bank Indonesia.Bouheni, F. B., & Houssem R. (2015). Bank capital adequacy requirements and risk-taking behavior in Tunisia: A simultaneous equations framework. The Journal of Applied Business Research, 31(1), 231-238.Dendrawijaya, L. (2009). Manajemen perbankan. Jakarta: Ghalia Indonesia.Fatimah, S. (2013). Pengaruh rentabilitas, efisiensi, dan likuiditas terhadap kecukupan modal bank umum syariah. Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 6(1), 42-58.Ghozali, I. (2011). Aplikasi analisis multivariate dengan program SPSS. Semarang: Universitas Diponegoro.Greuning, H. V., dan Iqbal, Z. (2011). Risk analysis for islamic banks: Analisis risiko perbankan syariah. Jakarta: Salemba Empat.Gujarati, D.N. (2006). Dasar-Dasar Ekonometrika Edisi 5 Jilid 1. Jakarta: Erlangga.Hempel, G. H., Coleman, A. B., & Simonson, D. G. (1986). Bank management, text and case. New York: John Wiley & Sons.Hengkeng, J. A. Walewangko, E. N., & Niode A. O. (2018). Analisis faktor-faktor yang mempengarui capital adequacy ratio bank sulut-go tahun 2002.I-2017.IV.Jurnal Berkala Ilmiah Efisiensi, 18(4), 84-95.Ikatan Bankir Indonesia (IBI) dan Banker Association for Risk Management (BARa). 2015. Manajemen risiko 1. Edisi 1. Jakarta: PT Gramedia Pustaka Utama.Johnson, F. P., & Richard, D. J. (1985). Commercial bank management. New York: The Dryden Press.Karim, A. A. (2004). Bank Islam: Analisis fiqih dan keuangan. Jakarta: RajaGrafindo Persada.Karim, A. A. (2007). Ekonomi makro Islami. Jakarta: Raja Grafindo Persada.Koch, T. W., & MacDonald, S. S. (2003). Bank management. Fifth Edition. Ohio: South-Western Thomson.Mankiw, N. G., Quah, E., & Wilson, P. (2014). Pengantar ekonomi makro: Edisi Asia. Jakarta: Salemba Empat.Mili, M., Sahut, J.M., Trimeche H., & Teulon, F. (2016). Determinants of the capital adequacy ratio of foreign banks’ subsidiaries: The role of interbank market and regulation. Research in International Business and Finance, 42(C), 442-453. http://dx.doi.org/doi:10.1016/j.ribaf.2016.02.002Muhammad. (2005). Manajemen bank syari’ah. Yogyakarta: UPP STIM YKPN.OJK. (2019). Statistik perbankan syariah. Jakarta: Otoritas Jasa Keuangan.___. (2015). Surat Edaran Otoritas Jasa Keuangan No. 34/SEOJK.03/2015 tentang perhitungan aset tertimbang menurut risiko untuk risiko kredit menggunakan metode standar bagi Bank Umum Syariah. Jakarta: Otoritas Jasa Keuangan.___. (2019). OJK Terapkan Perhitungan Risiko Pasar Basel III Terbaru. SP 02/DHMS/OJK/I/2019. Jakarta: Otoritas Jasa Keuangan.Shehzad, C. T., Haan, J.d., & Scholtens, B. (2010). The impact of bank ownership concentration on impaired loans and capital adequacy. Journal of Banking & Finance, 34(2), 399-408.Shingjergji, A., & Marsida, H. (2015). The determinants of the capital adequacy ratio in the Albanian banking system during 2007-2014. International Journal of Economics, Commerce and Management, 3(1), 1-10.Sutrisno. (2018). Factors determinant of bank capital buffer: empirical study on islamic rural banking in indonesia. Advances in Social Science, Education and Humanities Research. Proceedings of the 15th International Symposium on Management (INSYMA 2018).Taswan. (2013). Akuntansi perbankan: Transaksi dalam valuta rupiah. Edisi Tiga. Yogyakarta: UPP STIM YKPN.Umam, K. (2013). Manajemen perbankan syariah. Bandung: CV Pustaka Setia.UU RI. (2008). Perbankan Syariah. Jakarta: Undang-Undang Republik Indonesia.Wilara, G. R. dan Agus, T. B. (2016). Determinan ketahanan modal bank syariah di Indonesia: Pendekatan ECM. Jurnal Ekonomi & Studi Pembangunan, 17(2), 157-167.William, H. T. (2011). Determinants of capital adequacy in the banking sub-sector of the Nigeria eEconomy: Efficacy of camels. (A model specification with co-integration analysis).International Journal of Academic Research in Business and Social Sciences, 1(3), 233-248.Yolanda. (2017). Capital adequacy ratio and its influencing factors on the islamic banking in Indonesia.Journal of Islamic Economics and Business, 2(2), 162-176.